Czesław Miłosz w poszukiwaniu innej historyczności - Herlth, Jens (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article presents an analysis of the concept of “historicity”, which seems to be crucial for the understanding of the philosophical foundations of Miłosz’s work. The poet’s intention is to find a solution for the double dilemma of modern historical imagination: on the one hand, you should not become prey to the “murderous historicité”, but on the other, human life, when totally deprived of the historical dimension, seems to be empty and worthless. Miłosz found a solution of the dilemma in Stanisław Brzozowski’s philosophy, especially in his idea of of indispensability of historical consciousness, that is of “amplification” of historicity. The paradoxical, at first sight, attempt to overcome the disastrous consequences of historical thought through amplification of historicity itself, is seen in a wider contest of 20th-century philsophical investigations (Michaił Bachtin, Martin Heidegger, Barbara Skarga). It turns out that poetic discourse is the right place for its realization.